Determination of Species of Leishmania Using HSP70 Gene in Patients Referred to Selected Health Centers of Iran - Tahvildar Biderouni, Farid; Ali Bakhshi, Fatemeh; Taghipoor, Niloofar; Norouzi , Maryam (Novelty in Biomedicine, 2021)
Background: Cutaneous leishmaniasis is caused by Leishmania major and Leishmania tropaica. Iran is considered as one of the world’s largest leishmaniosis centers. In this study, the restriction fragment length polymorphism (RFLP)-PCR method was used to determine the species of pathogenic parasites. Materials and Methods: In this cross-sectional study, 120 patients with suspected cutaneous ulcer referring to the selected medical centers of Shahid Beheshti University of Medical Sciences were selected. Their demographic characteristics were recorded. After diagnosis of parasite by microscopy, positive samples were cultured in NNN medium. After DNA extraction of cultured parasite, PCR was performed for amplification of the HSP70 gene. The PCR products were digested with HaeIII restriction enzyme; the obtained patterns were compared with the same genes in the GenBank database. Results: A 1422 base pair fragment was detected in PCR of HSP70 gene in 30 positive samples. After digestion, 16 (53.3%) of the samples, had an enzymatic digestive pattern compatible to L. major and 14 (46.7%) others had the L. tropica profile. More information concerning demographic aspects were obtained after analyses them with the infected samples. Conclusion: Regarding the history of patient trips to their hometown, the transfer does not appear to have occurred in areas covered by the university’s medical centers, but the presence of these patients in these areas requires careful monitoring them. Additionally, control of population and mosquito species is needed. The results of this study sustain that the HSP70 gene still has sufficient ability to differentiate between two different species of L. major and L. tropica.